The need for malocclusion and treatment patterns of treatment in early children: Literature review: Kebutuhan perawatan maloklusi dan pola perawatannya pada anak usia dini: Kajian literatur - Donald R. Nahusona; Engella Chelsy Titania Patabang (Makassar Dental Journal PDGI Makassar, 2022)
Orthodontic treatment is a topic in dentistry that plays an important role in improving facial esthetics, function and stability of good treatment results.Interceptive treatment is orthodontic treatment that is performed in infancy or in the mixed dentition pe-riod to reduce the severity of the developing malocclusion in order to minimize the need for treatment. Interceptive treatment using functional appliance that produce orthopedic, dentoalveolar, andmusculoskeletal changes. Functional appliance, both fixed and removable types, can be used for skeletal correction in growing children. This literature reviewarticle is determined the need for malocclusion treatment and the pattern of needs in early childhood. The high need for interceptive orthodontic treatment may be caused by other factors, such as age, gender, level of parental knowledge, and socio-economic factors. It is concluded that class II malocclusion is the most dominant case in early children, which bad habit is one of the factors causing malocclusion. The need for malocclusion treatment at an early age is veryimportant so that the interceptive treatment pattern is needed by using functional appliance to prevent malocclusion become more severe.